2017
DOI: 10.1093/neuros/nyx355
|View full text |Cite
|
Sign up to set email alerts
|

Staged Stereotactic Radiosurgery for Large Brain Metastases: Local Control and Clinical Outcomes of a One-Two Punch Technique

Abstract: Staged radiosurgery is a safe and effective option for large, unresectable brain metastases. Prospective studies are required to validate the findings in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 22 publications
0
33
0
2
Order By: Relevance
“…Thus, staged SRS may be appropriate for tumors with a likelihood of rapid volume changes. The staged SRS technique was introduced for large metastatic brain tumors, in which the time interval between fractions ranged from 2 weeks to 1 month [16, 17]. This technique has the advantage of delivering the optimal dose to the target using interval imaging before each SRS as well as reducing the irradiated volume of the shrunken tumor after the first fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, staged SRS may be appropriate for tumors with a likelihood of rapid volume changes. The staged SRS technique was introduced for large metastatic brain tumors, in which the time interval between fractions ranged from 2 weeks to 1 month [16, 17]. This technique has the advantage of delivering the optimal dose to the target using interval imaging before each SRS as well as reducing the irradiated volume of the shrunken tumor after the first fraction.…”
Section: Discussionmentioning
confidence: 99%
“…As our main goal was to avoid surgery in symptomatic patients, we felt that Infini would be more suitable for obtaining a quicker tumor response that hopefully traduced in faster neurological improvement. Further studies are needed to compare multifraction LINAC versus multifraction Gamma Knife and the results provided by two-or three-session Gamma Knife in the treatment of large brain metastases [18][19][20]22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Radiosurgery apparently enhances the effects of low-dose steroids (e.g., 0.5 mg dexamethasone), resulting in rapid patient improvement. Our neoadjuvant radiosurgery protocol was replaced by the present study of two-session radiosurgery, inspired by staged radiosurgery schemes described by others, but with the hope to benefit not only those unsuitable for surgery, but rather those who could be operated by current recommendations standards [22][23]. It was exactly this group of patients for whom we sought to provide an apparent non-inferior, safe, effective, noninvasive alternative means of radiosurgery for rapid tumor response and control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local recurrence rates in these studies ranged from 12.1% to 15.0% and complication incidences from 1.9% to 6.4%, results very similar to those obtained with 3-st-GK-Tx. 1,2,5 The next question is whether 3-st-GK-Tx or 2-st-GK-Tx is the better option in terms of patient outcomes. Very recently, Serizawa et al reported a multi-institutional retrospective study designed to compare the treatment results of these 2 protocols (i.e., 3-stage or 2-stage treatment).…”
Section: Discussionmentioning
confidence: 99%